Infections due to rare Cryptococcus species: a literature review - Morales Lopez, Soraya E. (2021)
Infections due to rare Cryptococcus species (other than C. neoformans species complex, C. gattii species complex, C. albidus or C. laurentii) are barely reported. The aim of this work is to present a comprehensive literature review of all the papers describing infections due to these species referenced in the main databases (PubMed/MEDLINE, ScienceDirect, Scopus, and Google Scholar). Clinical and epidemiological data together with laboratory findings (identification and antifungal susceptibility) of each isolate were analyzed. Fifty-eight cryptococosis due to rare species were described in 46 papers between 1934-2018. These reports included 16 rare Cryptococcus spp. that were generally associated with nervous system infections and fungemias. Some species are non-capsulated and are not able to grow at 37 °C. Few species were identified by commercially available methods, making internal transcriber spacer (ITS) and D1/D2 regions sequencing mandatory. The most potent antifungal was amphotericin B (although some species showed high MIC values). The studied strains showed high MICs values to 5-fluorocytosine (all >64 µg/mL), echinocandins (all >8 µg/mL), and fluconazole (>80% of the MICs >4 µg/mL). Due to the scarcity of the data and the absence of guidelines for the treatment of these infections, this review could be informative and could help in the diagnosis and treatment of these infections.